Análisis de los ingresos del presupuesto General del Estado destinados a la Educación Superior período 2015 – 2020 - Rivera Bajaña, Karla Nathalia (2021)
At the level of Public institutions, the accrued budget is the economic values that were actually executed. They are administrative codes that are published through the Ministry of Economy and Finance of Ecuador. Income earned in Ecuador exceeded 20.4 billion in 2010, growing for 2019 to an amount of 36.7 billion dollars. On the other hand, accrued expenditures increased from 20.8 billion for 2010 to an amount of 34.8 billion for 2019. On the other hand, expenditures for Higher Education with an average participation of 3.2% in relation to the total expenses. When analyzing the relationship of the variables under study, the Pearson Correlation Coefficient tool indicates that there is a relationship of 0.82, being a positive result (Directly Proportional) and very close to +1. This means that your relationship or dependency is very significant…….